Pembelajaran dengan Pendekatan TaRL untuk Meningkatkan Minat dan Hasil Belajar Matematika Peserta Didik - Tanthowi Jauhari; Abdul Haris Rosyidi; Amik Sunarlijah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
Abstract: This research was motivated by the low interest and learning outcomes of class VIII-F students of SMP Negeri 54 Surabaya. Learning that is not in accordance with the abilities of students can cause students to be less active and experience a decrease in interest in learning. Low interest in learning can have an impact on low learning outcomes. Learning with the Teaching at the Right Level (TaRL) approach which does not refer to the class level can facilitate various characteristics of students. The research conducted in these 2 cycles aims to increase interest in and results in learning mathematics through the TaRL approach. TaRL emphasizes teachers to give students different treatment so that students' learning abilities and interests can develop according to their respective levels of development. Data on interest in learning were collected through questionnaires and data on learning outcomes through written tests, both of which were analyzed quantitatively. The indicator of the success of this research is that the percentage of students' interest in learning is included in the